Incidence and characterization of viruses infecting orchids in So Paulo state, Brazil - Moraes, Leticia A. [UNESP]; Krause-Sakate, Renate [UNESP]; Pavan, Marcelo A. [UNESP] (Springer, 2017)
Orchids are susceptible to a variety of abiotic and biotic agents that can affect their development and decrease the quality of their flowers and leaves. Viruses are one of the most important biotic agents, with Cymbidium mosaic virus (CymMV) and Odontoglossum ringspot virus (ORSV) as the most prevalent and of greater economic importance worldwide. Similar to a survey of virus infection in orchids carried out 20 years ago by Freitas et al. in the state of So Paulo, a new evaluation was made incorporating molecular methodologies on a total of 385 samples collected from commercial growers. Commercial antisera against CymMV, ORSV, Cymbidium ringspot virus, Tomato spotted wilt virus and viruses in the genus Potyvirus were used in ELISA tests. PCRs were performed to detect Orchid fleck virus (OFV) and primers were designed to amplify the coding region of the CymMV and ORSV capsid proteins. The most prevalent virus was CymMV, present in 274 samples (71.16%), followed by ORSV and OFV, present in 61 and 11 samples (15.85% and 2,85%), respectively. CymMV and ORSV capsid protein genes showed high sequence conservation. Symptoms caused by CymMV and ORSV have a great variability and are commonly confused with abiotic factors, nutritional problems and phytotoxicity.
Keywords: Cymbidium mosaic virus; Odontoglossum ringspot virus; Orchidaceae; Symptoms